TPACK perception analysis of teachers in facing 21st-century learning - Handi Suganda; Riandi Riandi; Widi Purwianingsih (Universitas Ahmad Dahlan, 2021)
This study aims to analyze and identify teachers 'perceptions of TPACK that can influence teachers' knowledge and understanding of 21st-century learning. The research method used in this research is the survey method with a cross-sectional research design. The research subjects consisted of 25 biology teachers with different teaching experiences ranging from learning experience ages less than 5 years to more than 15. The results showed that biology teachers with TPACK perceptions were quite good. Teachers 'perceptions of 21st-century learning are constrained by aspects of understanding students' abilities on creativity and critical thinking indicators. The consideration of teaching according to the skills demands of the 21st century is quite good. Teachers with low teaching experience still have less understanding of the latest learning technology. Each range of teacher teaching experiences has different abilities and perceptions and considerations of 21st-century learning that can become the foundation of teachers in implementing learning in the 21st century that puts forward the 4Cs aspect.